The relationship between the level of knowledge, documentation, and communication of nurses with the intra-hospital transfer process: A literature review - Masniari Juliana Siregar; Yufitriana Amir; Bayhakki Bayhakki (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: The intra-hospital transfer process is the transfer of patients while being treated in hospital from one service or from one inpatient unit to various other service units.Transfer is the transfer of a patient within the same facility for diagnostic procedures or transfer to another room to receive additional treatment. Purpose: This literature review aims to review previous research regarding the relationship between the level of knowledge, documentation and communication of nurses with the intra-hospital transfer process. Method: This literature review uses electronic databases such as PubMed, Google Scholar, Wiley Online Library, and Springer Link, which are journals published for the period 2016 to 2023. Articles were filtered using prism diagram rules, the keywords used in the literature search were